Speaking for the Shulhoyf: The Vilna Voices of Ayzik-Meyer Dik - Roskies, David G. (Colloquia, 2021)
When the Maskil Ayzik-Meyer Dik (ca. 1807–1893) retooled as a kritiker, a writer of satire, he did so by keeping it local. Most effectively, he exposed the evils and failings of the Jewish body politic by locating his satires in and around the crowded shulhoyf, the Great Synagogue and Courtyard, of his native Vilnius. Endowed with a phenomenal memory and a wicked sense of humour, there was no end to the gallery of schnorrers, shnorrerkes, rogues and misfits whom he could rescue from out of the recent, unenlightened past. But to speak for Jewish Vilna the way that Eugène Sue had spoken for Paris meant learning a new set of skills. To write popular fiction meant to draw upon the dialogical nature of language itself: the way low-lives and charlatans mimicked the speech of the learned class, while uncensored speech betrayed their boorishness, voracious appetites and debauchery; the way the speech of servant girls trafficked in the speech of their mistresses and outperformed them. Who spoke for the shulhoyf was the folksshrayber, the popular writer. Speech was dialogical, because to become a responsible folksshrayber required that one allow others to do the talking. Willy-nilly, and despite his professed ideology, Dik became the first writer to turn Ayalon-Linove-Vilna into the natural habitat of Yiddish.